Hukm al-Zawaj baina Mukhtalif al-Adyan fi Nadzariyyah al-Fuqaha - Dyabat, Etaher Ali Saad (Komparatif: Jurnal Perbandingan Hukum dan Pemikiran Islam, 2021)
Abstract:  This article discusses the jurisprudence of marriage between different religions in the theory of jurists. This normative legal research examines the law of interreligious marriage according to jurists and its effects. The research data was analyzed descriptively. The study concluded that the marriage of a Muslim woman to a Christian is not permissible in Islamic law. About the ruling on a Muslim marrying a woman from a biblical woman, the permissibility of a Muslim marrying a woman in writing is a desire for Islam. Still, this origin is considered with several restrictions, namely: 1- Making sure that she is biblical in the sense that she is a Jew or a Christian who believes in God and His messages and the hereafter and is not an atheist or apostate from her religion, and this is what abounds in the West. 2- To be chaste and immune. 3- There should be no fitna behind the marriage to the Scriptures or specific or likely harm. Concerning the ruling on a Muslim woman marrying a non-Muslim, the scholars are unanimous in prohibiting it. This is because Allah says in Surah Al-Baqarah: Verse 221. Keywords: interreligious marriage, jurists, Muslim, Muslim, jurisprudence.  الملخص:  يناقش هذا المقال عن حكم الزواج بين مختلف الأديان في نظرية الفقهاء. هذا البحث هو بحث قانوني معياري يبحث في قانون الزواج بين الأديان وفقا للفقهاء وآثاره. تم تحليل بيانات البحث بشكل وصفي. وخلصت الدراسة إلى أن زواجَ المسلمةِ من المسيحي غير جائز في الشريعة الإسلامية. وأما حكم زواج المسلم من الكتابية، إباحة زواج المسلم من الكتابية ترغيباً لها بالإسلام، ولكن هذا الأصل معتبر بعدة قيود وهي: 1- الإستيثاق من كونها كتابية بمعنى أنها يهودية أو نصرانية التي تؤمن بالله ورسالاته والدار الآخرة وليست ملحدة أو مرتدة عن دينها، وهذا ما يكثر في الغرب. 2- أن تكون عفيفة محصنة 3- ألا يكون من وراء الزواج من الكتابية فتنة ولا ضرر محقق أو مرجح. وأما حكم زواج المسلمة بغير المسلم، فقد أجمع العلماء على تحريمه. وذلك لقول الله تعالى في سورة البقرة: الآية 221. الكلمات المفتاحية: الزواج بين الأديان، الفقهاء، المسلم، المسلمة، الفقه